Use of a firebrand generator in the study of wildland and anthropogenic fires - Perminov, Vladislav V. (Journal of Physics: Conference Series)
In this paper in order to conduct a laboratory experiment on the effect of firebrands on the ground cover, the material under study was collected on the territory of the Tomsk region, namely the bark. The sizes of the samples simulating firebrands were chosen in accordance with the data of field experiments, according to the results of which it was noted that particles of precisely this size prevail during the transfer of fire. The experiments were carried out using an installation for the generation of firebrands. To determine the temperature of the particles generated by the installation, the experiment was recorded using an infrared camera. As a result of a series of experiments on the installation for the generation of firebrands, it was found that burning particles of pine bark, as well as pine twigs, are transported over a distance of 5–8 m at an average speed of 3.6 m/s. As a result, it was revealed that the probability of ignition of the ground cover depends on its density, as well as on the size of particles, their number and wind speed